Systemic Risk and Reinsurance - Tian, Weidong (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue covers the topic of timely vital risk management - systemic risk - from many important perspectives. It includes novel and scientific approaches from the network with topological indicators on systemic risk, community analysis of the global financial system, welfare analysis of capital insurance and the impact of capital requirement, risk measures, and optimal portfolio and optimal reinsurance under risk constraint. Most articles study the financial sector and insurance companies after the financial crisis of 2008-2009 circa ten years prior. The COVID-19 global pandemic in 2020 has caused similar or even greater challenges for the entire economy. Therefore, this Special Issue will be useful for anyone interested in systemic risk management.